Cigarrillos y malteada de chocolate: la Tobacco Plain Packaging Act australiana de 2011 - Tenorio D., Luis Felipe (2023)
n December 2011, Australia enacted the Tobacco Plain Packaging Act (TPP Act), which orders that the distribution of cigarettes be made in identical packs, with messages about the dangers of smoking and little space for brands. All of these packs were to use the same font and no distinctive elements. Big tobacco companies challenged the constitutionality of this act. These companies asked that, if the act were to be considered constitutional, it should not be applied to them because it would amount to an acquisition of property — industrial property in this case — on unjust terms. This article begins by telling the story of plain packaging. It then describe s the Australian legal system and the final decision that was made in this case. It concludes by presenting reflections on different aspects of the so - called new economy.